Arabidopsis-Green Peach Aphid Interaction: Rearing the Insect, No-choice and Fecundity Assays, and Electrical Penetration Graph Technique to Study Insect Feeding Behavior - Nalam, Vamsi (Bio-Protocol, 2018)

(untitled) (Bio Protoc)
Aphids constitute a large group of Hemipterans that use their slender stylets to tap into the sieve elements of plants from which they consume copious amounts of phloem sap, thus depriving the plant of photoassimilates. Some aphids also transmit viral diseases of plants. Myzus persicae Sülzer, commonly known as the green peach aphid (GPA), which is a polyphagous insect with a host range that covers 50 plant families, is considered amongst the top 3 insect pest of plants. The interaction between Arabidopsis thaliana and the GPA is utilized as a model pathosystem to study plant-aphid interaction. Here we describe the protocol used in our laboratories for rearing the GPA, and no-choice and fecundity bioassays to study GPA performance on Arabidopsis. In addition, we describe the procedure for the electrical penetration graph (EPG) technique to monitor feeding behavior of the GPA on Arabidopsis.